Banking in Germany: a short practical guide for the foreign banker by Martin Peltzer and Karl Nebendorf. - Peltzer, Martin; Nebendorf, Karl (Frankfurt (am Main) Knapp, 1973)
This book provides the international businessman - in particular the foreign banker- with an English language summary of the German banking system in a condensed and precise form.
English and German.
osc 19/9/17
Loans
Keywords: Banks and banking; Banking law; Banks and banking, Foreign